Kepuasan Sebagai Moderasi Pengaruh Citra Merek, Kepercayaan, dan Komitmen Terhadap Loyalitas Pelanggan Aplikasi Transportasi Online - Kartika Sari; Asyaroh Ramadona Nilawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The increasing business competition that exists requires business people to be more creative and innovative in creating new businesses and competitiveness, especially in the transportation business. Where today's people need transportation that is fast, safe, comfortable and easy to find. This research aims to determine the influence of satisfaction as a moderating influence of brand image, trust and commitment on customer loyalty of online transportation applications. The current analysis uses a quantitative approach. The results of this research have found that brand image, trust and commitment influence customer loyalty in online transportation applications. Satisfaction as moderation is able to moderate trust in customer loyalty of online transportation applications. However, satisfaction was not able to moderate brand image and commitment to customer loyalty of online transportation applications in this research.